Self-induced transparency and coherent population trapping of ⁸⁷Rb vapor in a mode-locked laser - Affolderbach, Christoph; Mileti, Gaetano; Masuda, Koji; Diels, Jean-Claude; Arissian, Ladan (My University, 2015)
Simultaneous self-induced transparency and a dark line resonance are observed inside a mode-locked laser. The circulating pulse, tuned to the 795-nm optical resonance of rubidium, has sufficient intensity to create at each passage a population inversion—return to ground state, typical of self-induced transparency. A drop in fluorescence (dark line resonance), is observed as the repetition rate is tuned to a submultiple of the hyperfine ground-state splitting.